Characteristics of granular sludge developed in an up-flow anaerobic sludge fixed film bioreactor treating palm oil mill effluent - Zinatizadeh, A.A.L.; Mohamed, A.R.; Mashitah, M.D.; Abdullah, A.Z.; Isa, M.H. (2007)
In the present study, characteristics of the granular sludge (including physical characteristics under stable conditions and process shocks arising from suspended solid overload, soluble organic overload, and high temperature; biological activity; and sludge kinetic evaluation in a batch experiment) developed in an upflow anaerobic sludge blanket fixedfilm reactor for palm oil mill effluent (POME) treatment was investigated. The main aim of this work was to provide suitable understanding of POME anaerobic digestion using such a granular sludge reactor, particularly with respect to granule structure at various operating conditions. The morphological changes in granular sludge resulting from various operational conditions was studied using scanning electron microscopy and transmission electron microscopy images. It was shown that the developed granules consisted of densely packed rod- (Methanosaeta-like microorganism; predominant) and cocci- (Methanosarsina) shaped microorganisms. Methanosaeta aggregates functioned as nucleation centers that initiated granule development of POME-degrading granules. Under the suspended solid overload condition, most of the granules were covered with a thin layer of fiberlike suspended solids, so that the granule color changed to brown and the sludge volume index also increased to 24.5 from 12 to 15 mL/g, which caused a large amount of sludge washout. Some of the granules were disintegrated because of an acidified environment, which originated from acidogenesis of high influent organic load (29 g chemical oxygen demand [COD]/L d). At 608C, the rate of biomass washout increased, as a result of disintegration of the outer layer of the granules. In the biological activity test, approximately 95% COD removal was achieved within 72 hours, with an initial COD removal rate of 3.5 g COD/L d. During POME digestion, 275 mg calcium carbonate/L bicarbonate alkalinity was produced per 1000 mg CODremoved/L. A consecutive reaction kinetic model was used to simulate the data obtained from the sludge activity in the batch experiment. The mathematical model gave a good fit with the experimental results (R2 > 0.93). The slowest step was modeled to be the acidification step, with a rate constant between 0.015 and 0.083 hours-1, while the rate constant for the methanogenic step was obtained to be between 0.218 and 0.361 hours-1.